Fungal population in wheat cultivars with different degrees of susceptibility to cereal soil-borne mosaic virus. - PRODI, ANTONIO; PISI, ANNAMARIA; RUBIES AUTONELL, CONCEPCION; TONTI, STEFANO; SANDALO, SILVIA; NIPOTI, PAOLA; C. Lanzoni; D. Rovito (2008)
Cereal soil-borne mosaic virus is widespread in Italy, especially in the northern and central regions, where it is known to cause grain yield reductions of up to 70% on the most susceptible cultivars of hexaploid wheat and durum wheat. Following reports indicating that the spread of FHB is greater in plants infected by barley yellow dwarf virus (BYDV) than in BYDV-free ones, we investigated the possibility of an analogous correlation between CSBMV and fungi having antagonistic and/or toxigenic activity. Four cultivars of bread wheat (Artico, Trofeo, Agadir, and Isengrain) and four of durum wheat (Neodur, Provenzal, Claudio, and Orobel), exhibiting a wide range of reactions to CSBMV, were grown in a in field near Cadriano (northern Italy) with natural inoculum sources of this virus. Mycoflora composition was investigated (CFU/g) in the rhizosphere soil and, towards the end of the wheat growth cycle, also in roots, stems, and seeds. Fusaria species were identified molecularly. The fungi isolated from the soil were mostly saprophytes. Penicillium was found mainly in May, whereas Fusaria were most abundant in July; the antagonistic Trichoderma was not detected. Fusaria were detected in the seeds of all cultivars and were most abundant in durum wheat cultivars Orobel (17%), susceptible to CSBMV, and Provenzal (12%), resistant to the virus. Several Fusarium species were identified: F. culmorum prevailed in durum wheat and F. poae in bread wheat. Preliminary data suggest that there is no correlation between fungal colonization and susceptibility to CSBMV of the withering plants. Further studies are in progress.